1983
DOI: 10.1136/adc.58.12.997
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of cerebral function after severe asphyxia in infancy.

Abstract: SUMMARY Thirty nine infants with severe asphyxia (28 affected perinatally and 11 later) were studied by electrophysiological cerebral function monitoring (CFM) for periods varying from a half to 49 days. Nineteen infants died while still in intensive care and two died later from sequelae. Eighteen survived and were followed up when aged between 8 and 36 months. The initial electroencephalogram (EEG) and the first 12 hours of CFM tracing correlated well. The type of background activity, whether continuous or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
37
0
3

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(43 citation statements)
references
References 17 publications
3
37
0
3
Order By: Relevance
“…There was a good agreement between conventional EEG and aEEG recordings, similar to previous studies (8,12,14). Conventional EEG provided additional information in only two infants, showing focal EA that was not identified on aEEG.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…There was a good agreement between conventional EEG and aEEG recordings, similar to previous studies (8,12,14). Conventional EEG provided additional information in only two infants, showing focal EA that was not identified on aEEG.…”
Section: Discussionsupporting
confidence: 69%
“…When aEEG background patterns were of normal voltage (CNV, DNV) or normalized before the age of 24 h, prognosis was fair, whereas severely abnormal aEEG patterns that persisted beyond that age were related to adverse outcomes. Previous studies have shown that, already several hours after birth, aEEG recording is a reliable method for early prediction of neurologic outcome in asphyxiated infants, with accuracy between 70 and 85% (8,11,12,26). Our findings indicate that extension of the recording period up to 48 h after birth adds to the prognostic value.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations